(untitled) (European Journal of Economics, Finance and Business Development, 2025)
The article is devoted to the analysis of such concepts as “self-defense of the employee’s labor rights, implementation of ongoing reforms in this area, filling gaps in the legislation”, improvement of current legislative documents in this area, as well as increasing efficiency in the field of self-defense of the labor rights of employees using the latest information systems.